Performance analysis of NOMA uplink transmission over generalized-K fading channels - Aslan, Kardes; Gucluoglu, Tansal (WILEY, 2022)
Non-orthogonal multiple access (NOMA) can serve multiple users in the same time slot and frequency band and thus eliminate the need for guard bands and guard intervals to provide significant capacity improvements. Therefore, the research on its performance has been increasing since it is a desirable candidate for next-generation wireless networks. Compared with orthogonal multiple access (OMA) techniques, the reliability of NOMA is lower since multiple access interference increases as the number of users is increased. Most of the previous studies on NOMA systems only consider the impact of fading in the transmission medium; however, more realistic channel models include both fading and shadowing. In this paper, outage probability (OP), average channel capacity, and symbol error rate (SER) for uplink NOMA over generalized-K fading are derived analytically for the arbitrary number of users and then verified by Monte Carlo simulations.
Keywords: generalized-K fading channels; non-orthogonal multiple access; outage probability; symbol error rate; ERROR RATES; OUTAGE PERFORMANCE; SYSTEMS; SIGNALS; Engineering; Telecommunications